EFFECTIVENESS OF AUDIO-VISUAL TEACHING LEARNING MATERIALS ON ACADEMIC ACHIEVEMENT AT THE SECONDARY LEVEL: A SYSTEMATIC LITERATURE REVIEW AND META-ANALYSIS - K, Kalyani; N, Roopa A; T D, Dr. Praveen Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Audio-visual teaching and learning materials have become increasingly prevalent in secondary education, yet a comprehensive synthesis of their effectiveness on academic outcomes remains limited. This systematic literature review and meta-analysis aimed to evaluate the impact of audio-visual materials on academic achievement, retention, engagement, and attitudes among secondary-level students. We systematically identified and synthesised evidence from 31 empirical studies, extracting standardised mean differences and corresponding standard errors for meta-analytic integration. The analyses employed random-effects models to account for heterogeneity across study contexts. For the primary outcome of academic achievement and retention, the pooled effect size was substantial (d=0.85, 95% I [0.78, 0.92], p<1e^(-5)), indicating a large positive effect. For engagement and attitude measures, the overall effect was moderate (d=1e to the [0.37, 0.45], p<1e^(-5)). Furthermore, the availability of audio-visual materials also yielded a moderate pooled effect (d=0.52, 95% I [0.37, 0.66], p<1e^(-5)). These findings collectively suggest that audio-visual materials significantly enhance academic performance and foster positive learner engagement at the secondary level. The results underscore the value of integrating such resources into instructional practices, although variability in effect sizes across studies warrants careful consideration of implementation factors. Future research should explore moderating variables and long-term retention effects.